Neighboring cells override 3D hydrogel matrix cues to drive human MSC quiescence. (September 2018) - Ferreira, Silvia A.; Faull, Peter A.; Seymour, Alexis J.; Yu, Tracy T.L.; Loaiza, Sandra; Auner, Holger W.; Snijders, Ambrosius P.; Gentleman, Eileen
Abstract: Physical properties of modifiable hydrogels can be tuned to direct stem cell differentiation in a role akin to that played by the extracellular matrix in native stem cell niches. However, stem cells do not respond to matrix cues in isolation, but rather integrate soluble and non-soluble signals to balance quiescence, self-renewal and differentiation. Here, we encapsulated single cell suspensions of human mesenchymal stem cells (hMSC) in hyaluronic acid-based hydrogels at high and low densities to unravel the contributions of matrix- and non-matrix-mediated cues in directing stem cell response. We show that in high-density (HD) cultures, hMSC do not rely on hydrogel cues to guide their fate. Instead, they take on characteristics of quiescent cells and secrete a glycoprotein-rich pericellular matrix (PCM) in response to signaling from neighboring cells. Preventing quiescence precluded the formation of a glycoprotein-rich PCM and forced HD cultures to differentiate in response to hydrogel composition. Our observations may have important implications for tissue engineering as neighboring cells may act counter to matrix cues provided by scaffolds. Moreover, as stem cells are most regenerative if activated from a quiescent state, our results suggest that ex vivo native-like niches that incorporate signaling from neighboring cells may enable the production of clinically relevant, highly regenerative cells.